Răspuns :
Răspuns:
Explicație pas cu pas:
E(- 3) = [4 × (- 3) + 3]² + [2 × (- 3) - 4][4 × (- 3) + 3] + (- 3 - 2)²
E(- 3) = (- 12 + 3)² + (- 6 - 4)(- 12 + 3) + (- 5)²
E(- 3) = (- 9)² - 10 × (- 9) + 25
E(- 3) = 81 + 90 + 25
E(- 3) = 171 + 25 = 196 = 14² ∈ N
Explicație pas cu pas:
[tex]E(x) = (4x + 3)^{2} +(2x - 4)(4x + 3) + (x-2)^{2} \\ = 16{x}^{2} + 24x + 9 + 8 {x}^{2} + 6x - 16x - 12 + {x}^{2} - 4x + 4 \\ = 25 {x}^{2} + 10x + 1 = {(5x + 1)}^{2} [/tex]
[tex]=> E(x) = {(5x + 1)}^{2} [/tex]
[tex]E(-3) = {(5( - 3) + 1)}^{2} = {( - 14)}^{2} = {14}^{2} \\ = > E(-3) = {14}^{2} [/tex]